Skema Kompetitif sebagai Sistem Standarisasi Gaji ASN - Akbar, Fachreza Nur Masrik; Ismatiah, Maulita Azizah (Peneliti.net, 2024)
The ASN salary issue, which has become a routine discussion every year, is again a hot topic. Workers feel that the salary increase of no more than 10% is not equivalent to the work responsibilities of employees. In addition, the performance that has been given is also still contrary to the basic salary received equally for all employees. ASN salaries, the majority of which are still below the average UMR, are certainly an important issue that has received many complaints from government employees. In connection with this issue, the PANRB Ministry is trying to find a solution by starting to carry out a new system related to ASN salaries so that they can be competitive when compared to BUMN salaries. This study was conducted to analyze the implementation of the ASN basic salary system and respond to the issue of equalizing ASN salaries with BUMN workers. By taking a qualitative approach, the analysis was carried out with additional sources of discussion using the concept of systematic literature review.